1970
DOI: 10.1159/000252467
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol in Psoriasis

Abstract: We have tried Allopurinol in the treatment of psoriasis, without having any knowledge of previous publications in this respect. The antigouty drug, which acts inhibiting the xanthine oxidase has proved excellent in 50%, good in 34% and moderate in 16% of the cases treated, independent of the oldness of the process. This study constitutes a new step in the metabolic pathogenesis of psoriasis which has already been the motive of other investigatory works by the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Moreover, even if there were no distinct rebound phenomena, some worsening of the condition might have been expected in the two patients who had received allopurinol first and improved, barring a very protracted 'carry-over' effect (Rinzler et al, 1953). We are thus inclined to believe that the absence of a rebound phenomenon, as stressed by Viglioglia et al (1970), is a feature of the natural course of psoriasis, as in our case 6, who commenced to clear rapidly on the placebo, and in whom new lesions appeared at the end of the allopurinol period.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, even if there were no distinct rebound phenomena, some worsening of the condition might have been expected in the two patients who had received allopurinol first and improved, barring a very protracted 'carry-over' effect (Rinzler et al, 1953). We are thus inclined to believe that the absence of a rebound phenomenon, as stressed by Viglioglia et al (1970), is a feature of the natural course of psoriasis, as in our case 6, who commenced to clear rapidly on the placebo, and in whom new lesions appeared at the end of the allopurinol period.…”
Section: Discussionmentioning
confidence: 98%
“…
In this double-blind cross-over study allopurinol was found to be no more eifective than a placebo in the treatment of psoriasis.The report of Viglioglia et al (1970) on the effectiveness of allopurinol in the treatment of psoriasis prompted us to undertake this double-blind cross-over study on the effect of allopurinol and a placebo in psoriatic patients.
MATERIAL AND METHODSSixteen patients aged 32-63 years were initially included in the study. Thirteen of them (eight males and five females) completed the study.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65] The effectiveness of allopurinol in the treatment of psoriasis has been reported. [53,66] In Russia, a study suggested that allopurinol can be beneficial in treating psoriasis; 63 of 147 patients (42.8%) who had received allopurinol together with other antipsoriatic treatments demonstrated an increase in therapeutic effects compared with 46 of 147 patients (31.3%) who did not receive oral allopurinol. [53] However, a small, double-blind, crossover study failed to demonstrate effectiveness.…”
Section: Allopurinol In Dermatologymentioning
confidence: 99%
“…A few reports have appeared of excellent results mth the xanthine oxidase inhibitor allopurinol, which is of interest in view of the high urie acid levels found in many patients (Bradford and Hrehorovitch, 1969). Toxicity is minimal, and the drug may be stopped without severe rebound (Viglioglia et al, 1970). Other antimetabolites, which have been used sporadically without full trial or comparison, include triaeetj'l azauridine (Calabresi and Turner, 1966), azaribine (Vogler and Olansky, 1970), and busulfan (Moller and Waldenstrom, 1970).…”
mentioning
confidence: 99%